(untitled) (Semiárida, 2018)
For cases in which there is a need to design a teaching project, the main foundations tobe considered for its structure becomes a matter not always entirely clear. When the studysubject involves complex interactions among the various factors playing a role as systemcomponents, it is essential to define the bases a project will be relying on. In this regard,its organization on the grounds of precise assessing of objectives, contents, activities andevaluations can be very useful for teaching line up and learning process fulfillment.